Simulation Coordination Control of PVAnd Battery On Microgrid With PI Controller - Adhi Kusmantoro; Takashi Hiyama (Universitas Negeri Semarang, 2023)
Purpose: The output power of PV (photovoltaic) changes according to changes in the intensity of solar radiation. Therefore, the purpose of this study is to use a utility grid connected system to overcome changes in solar energy sources and loads. This is done to maintain an uninterrupted power supply to the load.Methods: In this study, we propose a grid-connected PV system with several DC-DC converters connected in parallel with several PV sources and batteries with PI control coordination. The proposed method includes two stages, namely the DC-DC converter development stage and the battery management strategy stage.Results: The study results show that within 0 seconds to 0.45 seconds the DC bus is supplied with PV. Due to the change in PV, within 0.45 seconds to 0.65 seconds the DC bus is supplied with unit-1 battery. When there is a change in the unit-1 battery, within 0.65 seconds to 0.8 seconds the DC bus is supplied with the unit-2 battery. By using PV coordination arrangements and battery units, the microgrid can still supply power to the load even if changes occur in the PV or grid.Novelty: The novelty in this study is a new microgrid configuration to increase the demand for electrical loads. The new configuration uses multi-PV and multi-battery. Multi-PV is used to supply the load and is stored in the multi-battery, while multi-battery is used at night and if there is a disturbance at the PV output.